Evolution of a degree program: the Australian example. - Baird M (Radiologic Technology)
The progression of undergraduate radiography programs from diploma to bachelor's degree level has become a reality in Australia. This article outlines the evolution, underlying philosophy and structure of the bachelor of applied science in medical radiations program conducted by the Department of Medical Radiations Science at the Royal Melbourne Institute of Technology.